A preliminary study on the recommended fitness test on students with visually-impaired: An alternative to SEGAK? - Abdullah, Nagoor Meera; Mt Desa, Siti Nurfarahah; Mohd Pilus, Asiah; Tumijan, Wahidah; Mohamed Shapie, Mohamad Nizam (Jurnal Pendidikan Bitara UPSI, 2020)
SEGAK Test (Standard Kecergasan Penilaian Kebangsaan) known as the fitness test for students in Malaysia, but the test relevancy with students with disabilities can be questioned. For that, an effort been taking to design a test battery specifically for students with visually-impaired. Purpose of the study was to investigate the differences of fitness level on fitness test protocols on students with visual impairments. For the preliminary study, a total of thirty students (N=30) were selected where 14 were females and 16 were male students aged between 13 to 19 years old and all the participants currently are studying at Sekolah Menengah Pendidikan Khas (cacat penglihatan) Setapak, Kuala Lumpur. The participants were divided into three (3) groups based on the visual impairments classes which are B1, B2 and B3. Therefore, B1 had 12 participants, B2 had 15 participants and B3 had three (3) participants. All the participants were tested with the fitness tests that are a) one-mile run/walk test, b) curl up test, c) isometric push up test and d) sit and reach test. The results revealed that there was no significant difference in BMI, isometric push up, curl up, one-mile run/walk and sit and reach (p > 0.05). In a conclusion, a test battery needs to be designed for students with disabilities especially students with visually-impaired.